(untitled) (Innovaciones Educativas, 2023)
This article is the result of the follow-up of vocational pathways of the graduates during 2016-2021 of Veritas University, and the general objective was to describe the vocational trajectory of this population, from the theory of career construction and life design. The methodology was from a quantitative approach and a descriptive cross-sectional design, the sample was probabilistic stratified by proportional allocation (n=480) and a digital form was used as an instrument. The results indicate that the majority of the sample was lagging behind at the time of graduation, the average academic performance was 87. More than half did not work while studying, about half continued studying after graduation and most of them want to go to university; besides, the employment rate is high. From those who are employed, most work for the private sector, do not hold managerial positions, have only one job, and perceive stability, satisfaction, career-job relationship, and contribution of the career to employment. It is concluded that the vocational pathway is characterized by academic lag, few spaces for professional practice during training, high academic performance, desire to be linked to the university, positive indices of job satisfaction, job stability, relationship with the career and income; but permeated by a percentage of unemployment enhanced by the economic crisis resulting from the pandemic. Therefore, it is recommended to reform the curricula, continue strengthening the professional internship project and formalize the Professional Guidance service.